Chemoselective anti-Markovnikov hydroamination of alpha,beta-ethylenic compounds with amines using montmorillonite clay - Joseph, Trissa; Shanbhag, G. V.; Sawant, D. P.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A-Chemical, 2006)
The catalytic activity of montmorillonite clays as a catalyst for the hydroamination of alpha,beta-ethylenic compounds with amines was tested. Aniline and substituted amines reacted with alpha,beta-ethylenic compounds in the presence of catalytic amount of commercially available clay to afford exclusively anti-Markovnikov adduct in excellent yields. Aniline reacted with ethyl acrylate to yield only anti-Markovnikov adduct N-[2-(ethoxycarbonyl)ethyl] aniline (mono-addition product). No Markovnikov adduct (N-[1-(ethoxycarbonyl)ethyl]aniline and double addition product N,N-bis[2-(ethoxycarbonyl)ethyl]aniline were formed under selected reaction conditions. For a better exploitation of the catalytic activity in terms of increased activity and improved selectivity for the mono-addition product, the reaction parameters were optimized in terms of temperature, solvent, reactant mole ratio. Under optimized reaction conditions, montmorillonite clay K-10 showed a superior catalytic performance in the hydroamination of ethyl acrylate with aniline with a conversion of aniline to mono-addition product (almost 100% chemoselectivity) with a high rate constant 0.3414 min(-1) compared to the reported protocols. The dependence of conversion of aniline over different types of montmorillonite clays (K-10, K-20, K-30, Al-Pillared clay and untreated clay) has also been discussed. The activities of clay for the hydroamination of different aromatic and aliphatic amines have also been investigated. Under harsh reaction conditions (increased temperature and long reaction time) small amounts of di-addition products were observed. The kinetics data has been interpreted using the initial rate approach model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alpha; amines; anti-Markovnikov addition product; beta-ethylenic compounds; chemo-selective; hydroamination; K-10 montmorillonite clay

Potassium phosphate or silica sulfuric acid catalyzed conjugate addition of thiols to alpha,beta-unsaturated ketones at room temperature under solvent-free conditions - Pore, D. M.; Soudagar, M. S.; Desai, Uday V.; Thopate, T. S.; Wadagaonkar, P. P. (Tetrahedron Letters, 2006)
Potassium phosphate and silica sulfuric acid have been found to be useful and highly efficient catalysts for conjugate addition of thiols to alpha,beta-unsaturated ketones under solvent-free conditions, at room temperature. Silica sulfuric acid (SSA) was found to be suitable for electron-deficient enones while potassium phosphate was found to effect thia-Michael addition with both, electron-deficient as well as electron-rich conjugated ketones. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha; beta-unsaturated ketones; chalcones; conjugated enones; Michael addition; Potassium phosphate; silica sulfuric acid; thiols

Chemoselective hydrogenation of cinnamaldehyde over Pd/CeO2-ZrO2 catalysts - Bhogeswararao, Seemala; Srinivas, D. (Catalysis Letters, 2010)
Selective hydrogenation of cinnamaldehyde over Pd (2 wt%) supported on CeO2, ZrO2 and CeO2-ZrO2 catalysts is reported for the first time. In general, the olefinic (C=C) group of cinnamaldehyde is preferentially hydrogenated compared to the carbonyl (C=O) group. This selectivity preference could, however, be altered or reversed by adding alkali additives to the catalyst. The influence of additive on the structure and redox properties of the active sites and correlation of that with selective hydrogenation activity is investigated.
Keywords: alpha; beta-Unsaturated aldehyde; Ceria-zirconia; Cinnamaldehyde; Hydrogenation; palladium catalyst

Effect of particle size on selective hydrogenation of cinnamaldehyde by Pt encapsulated in mesoporous silica - Prashar, Atul K.; Mayadevi, S.; Devi, R. Nandini (Catalysis Communications, 2012)
Pt nanoparticles of various sizes, viz. 8. 4.9, 3.6 and 1.8 nm were encapsulated in 2D hexagonal mesoporous silica by in-situ synthesis as well as post synthetic modifications so that the final catalyst composition was <= 1 wt.% Pt/SiO2. A kinetic analysis of the effect of particle size on selective hydrogenation of cinnamaldehyde was carried out on these catalysts. It was found that the materials, even at such low loading of Pt, were very active for the hydrogenation and selective for the desired product, cinnamyl alcohol. Among the different particle sizes, selectivity was found to be the highest on 8 nm particles. Kinetic analysis shows that the reaction follows a consecutive reaction pathway. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: alpha; beta-Unsaturated aldehydes; Cinnamaldehyde hydrogenation; Kinetic analysis; Mesoporous silica; Pt nanoparticles; Selective hydrogenation

Intramolecular selective hydrogenation of cinnamaldehyde over CeO2-ZrO2-supported Pt catalysts - Bhogeswararao, Seemala; Srinivas, D. (Journal of Catalysis, 2012)
Selective liquid phase hydrogenation of cinnamaldehyde is reported, for the first time, over CeO2, ZrO2, and CeO2-ZrO2-supported Pt catalysts. Cinnamyl alcohol is the selective product. These catalysts are highly active and selective even at 25 degrees C and found to be superior to most of the hitherto known supported Pt catalysts. Alkali addition (NaOH) has enhanced the performance of these catalysts. At an optimized reaction condition, 95.8% conversion of cinnamaldehyde and 93.4% selectivity of cinnamyl alcohol have been obtained. Acidity of the support (due to the presence of ZrO2 component) and higher electron density at Pt (due to CeO2 component) are attributed to be responsible for the superior catalytic activity of Pt supported on CeO2-ZrO2 composite material. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: alpha; beta-Unsaturated aldehyde; Ceria-zirconia; Cinnamaldehyde; Hydrogenation; Promotion by alkali ions; Supported Pt catalyst

Regioselective synthesis of 1,4,5-trisubstituted 1,2,3-triazole derivatives from alpha,beta-unsaturated carbonyls - Verma, Naimish K.; Bera, Smritilekha; Gonnade, Rajesh; Mondal, Dhananjoy (European Journal of Organic Chemistry, 2022)
The copper-catalyzed oxidative azide-olefin cycloaddition (OAOC) reaction of differently substituted alpha,beta-unsaturated carbonyls with azides provided an efficient method for preparing biologically active 1,4,5-trisubstituted 1,2,3-triazoles. In this study, the cycloaddition reaction was found to be a simple and powerful method for constructing diverse mono- and bis-(1,4,5-trisubstituted 1,2,3-triazole) functionalized heterocyclic compounds in moderate to high yields with great regioselectivity. The XRD-analysis data of one of the bis-triazole derivatives supported the regioselectivity as well as the conformity of the method in the construction of the triazole nucleus. The preliminary antifungal profile against C. albicans was observed with cinnamaldehyde-based triazole derivatives demonstrating promising results.
Keywords: alpha; antifungal; beta-Unsaturated carbonyls; Cycloaddition; Dibenzalacetone; Triazole

Manganese-catalyzed chemoselective direct hydrogenation of α,β-epoxy ketones and α-ketoamides at room temperature - Shabade, Anand B.; Singh, Rahul K.; Gonnade, Rajesh G.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
Chemoselective hydrogenation of alpha,beta-epoxy ketones and alpha-ketoamides is achieved at room temperature (25 degrees C) using 2.0 bar H-2 and a pincer-ligated Mn(I) catalyst that provides synthetically valuable alpha-hydroxy epoxides and alpha-hydroxy amides. This protocol applies to a wide range of alkyl- and aryl-substituted alpha,beta-epoxy ketones, including terpenes (alpha-ionone, nootkatone, and R-carvone)- and steroids (testosterone and progesterone)-derived epoxy ketones, and tolerates H-2 sensitive functionalities, such as halides, acetyl, nitrile, nitro, epoxide, alkenyl and alkynyl groups. Additionally, alpha-ketoamides bearing reducible functional groups, including acetyl and diazo benzene, were untouched under this protocol and selectively converted to alpha-hydroxy amides. A preliminary mechanistic study highlighted the metal-ligand cooperative H-2 activation process.
Keywords: alpha; beta-epoxy ketones; chemoselectivity; direct hydrogenation; manganese; Metal-ligand cooperation